PENGARUH PEMBERIAN UMBI BENGKUANG (Pachyrrhizus erosus l urban) TERHADAP JUMLAH PIGMEN MELANIN KULIT MENCIT (Mus musculus) YANG DIPAPARKAN SINAR MATAHARI - I H, Siti Fitrah; Lintong, Poppy M.; Loho, Lily L. (Universitas Sam Ratulangi, 2015)
Abstract: Exposure to sunlight causes melanocytes activity increased so as to increase the production of melanin pigment. Yam (Pachyrrhizus erosus l urban ) contains vitamin C and starch that are opaque can be used to protect the skin from sun exposure. This study aimed to determine the effect of yam tubers to the amount of melanin pigment of skin of mice exposed to sunlight. The method used in this study is an experimental laboratory to the subject of 20 mice were divided into 4 groups. A group is a negative control, B group mice were given exposure to the sun for 20 days. C group mice jicama juice smeared then exposed to sunlight for 20 days, group D mice exposed to sunlight and then stopped after 20 days followed by administration of yam 10 days. The results of group A has an average number of pigment 7, group B 89.5, group C 36, and group D 7,5. In conclusion exposure to sunlight increases the amount of melanin pigment and giving yam decreases the amount of melanin pigment.Keywords: sunlight, yam, melanin pigmentAbstrak: Paparan sinar matahari menyebabkan aktivitas melanosit meningkat sehingga dapat menambah produksi pigmen melanin. Bengkuang (Pachyrrhizus erosus l urban) mengandung vitamin C dan pati yang bersifat opaque dapat dimanfaatkan untuk melindungi kulit dari paparan sinar matahari. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian umbi bengkuang terhadap jumlah pigmen melanin kulit mencit yang dipaparkan sinar matahari. Metode yang digunakan pada penelitian ini adalah experimental laboratorik dengan subjek 20 ekor mencit yang terbagi dalam 4 kelompok. Kelompok A merupakan kontrol negatif, kelompok B mencit diberi paparan sinar matahari selama 20 hari. Kelompok C mencit dioleskan jus bengkuang lalu dipaparkan sinar matahari selama 20 hari, kelompok D mencit dipaparkan sinar matahari lalu dihentikan setelah 20 hari dilanjutkan dengan pemberian bengkuang 10 hari. Hasilnya kelompok A memiliki jumlah pigmen rata-rata 7, kelompok B 89,5, kelompok C 36, dan kelompok D 7,5. Kesimpulannya paparan sinar matahari meningkatkan jumlah pigmen melanin dan pemberian bengkuang menurunkan jumlah pigmen melanin.Kata kunci: sinar matahari, bengkuang, pigmen melanin